Entrepreneurship : Spices & Herbs Paradise / Nor Hasanah Yaakub ... [et al.] - Yaakub, Nor Hasanah; Ibrahim, Nor Suriati; Hassan, Norhazlinda; Abd. Aziz, Nor Ismawati; Ramia, Nor Fauziah (2001)
The spices and herbs paradise is operating as one of the marketing company that focus on selling herbal and spices product. The objective of our business is to introduce for our new generation to be more concern about the important and function of herbs and spices. It is in form of fives partner base on partnership rules.